Combustion characteristics and fire hazard of polystyrene exterior wall thermal insulation materials. Issue 8 (5th December 2022) - Ouyang, Dihua; Yan, Haoyu; Song, Jiaxing; Yang, Chunhai; Jiang, Tao; Liu, Chengkui
Abstract: To study the combustion characteristics and fire hazard of polystyrene building exterior wall thermal insulation materials, the combustion, fire, and pyrolysis characteristics of thermosetting polystyrene (TPS) insulation, graphite polystyrene (GEPS), and expanded polystyrene (EPS) are compared and analyzed using a cone calorimeter and a thermo‐gravimetric analyzer. From the structure and flame retardant components of thermal insulation board, their flame retardant mechanisms are described. Results show that in a nitrogen atmosphere, the pyrolysis range is 30–600°C. Only one weight loss stage in EPS and GEPS and two weight loss stages in TPS are observed. Comparison of the combustion characteristics of the three demonstrates that TPS has short ignition time, low fire performance index. This result indicates that TPS has the characteristics of good flammability and easy to explode. The smoke generation rate, total smoke production, time heat release index and total heat release of TPS are lower than those of EPS and GEPS. This result indicates that the fire thermal hazard and fire smoke risk of TPS are relatively small. Comparison of various indexes presents that the flammability and fire risk of TPS are evidently better than those of EPS and GEPS.